PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP HASIL BELAJAR MATERI BANGUN RUANG PADA SISWA KELAS VI SEKOLAH DASAR - Imandha, Achmad Firmansyah Putra; Yuhana, Yuyu; Firdaus, Firdaus (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to analyze the effect of contextual learning on sixth-grade students’ learning outcomes on the topic of three-dimensional shapes (cubes and rectangular prisms). The research employed a quantitative quasi-experimental approach using a non-equivalent control group design. The population consisted of all sixth-grade students at SDN Malaka Jaya 08 Pagi. The sample included an experimental class using contextual learning and a control class using conventional learning. Data were collected through pretest and posttest essay tests (10 items) and observation. Data analysis included tests of normality, homogeneity, t-test, and normalized gain (N-gain). The results showed a significant difference between the two groups. In the control class, the mean score increased from 24.17 (pretest) to 57.43 (posttest), with an N-gain of 0.47 (moderate, less effective). In contrast, the experimental class improved from 24.93 to 84.80, with an N-gain of 0.79 (high, effective). The t-test results indicated a probability value < 0.05, confirming a significant difference. In conclusion, contextual learning has a significant and more effective impact on improving students’ learning outcomes compared to conventional methods.